Pediatric complex care and surgery comanagement: Preparation for spinal fusion. (September 2020) - Berry, Jay G; Glaspy, Tyler; Eagan, Brian; Singer, Sara; Glader, Laurie; Emara, Norah; Cox, Joanne; Glotzbecker, Michael; Crofton, Charis; Ward, Erin; Leahy, Izabela; Salem, Joseph; et al.
The aim of this study is to assess the impact of preoperative comanagement with complex care pediatricians (CCP) on children with neuromuscular scoliosis undergoing spinal fusion. We performed chart review of 79 children aged 5–21 years undergoing spinal fusion 1/2014–6/2016 at a children's hospital, with abstraction of clinical documentation from preoperative health evaluations performed regularly by anesthesiologists and irregularly by a CCP. Preoperative referrals to specialists, labs, tests, and care plans needed last minute for surgical clearance were measured. The mean age at surgery was 14 (SD 3) years; cerebral palsy (64%) was the most common neuromuscular condition. Thirty-nine children (49%) had a preoperative CCP evaluation a median 63 days (interquartile range (IQR) 33–156) before the preanesthesia visit. Children with CCP evaluation had more organ systems affected by coexisting conditions than children without an evaluation (median 11 (IQR 9–12) vs. 8 (IQR 5–11); p < .001). The rate of last-minute care coordination activities required for surgical clearance was lower for children with versus without CCP evaluation (1.8 vs. 3.6). A lower percentage of children with CCP evaluation required last-minute development of new preoperative plans (26% vs. 50%, p = .002). Children with CCP involvement were better prepared for surgery, requiring fewer last-minute care coordination activities for surgical clearance.